Challenging the Status Quo: Disability in Australian Children’s Picture Books - Glasby, Karen (Archīum Ateneo, 2025)
This article will analyze a range of Australian picture books that both explore the topic of disability and serve as educational tools for exploring diversity issues. The books were identified in a survey administered by the State Library of New South Wales (NSW) public library service, which identified 62 books that deal with diversity. Thirteen of the 62 books were assessed as having characters with a disability—including autism, mental illness, dementia, spina bifida, neurodiversity, physical disability, deafness, and implied but unidentified disabilities. This article will analyze the approach adopted in each of the picture books using Rudine Sims Bishop’s three categories of multicultural literature criticism—Social Conscience, Melting Pot, and Culturally Conscious. By doing so, the article will assess the extent to which picture books offer an authentic exploration of disability in step with broader educational developments.